Successful long‐term management of spasticity in people with multiple sclerosis using a software application: Results from a randomized, controlled, multicenter study. (14th February 2022) - Ehling, Rainer; Seebacher, Barbara; Harsányi, Andrea; Ganzbiller, Nicole; Papez, Stephanie; Haider, Bernhard; Hoertenhuber, Doris; Kranz, Gottfried; Tarasiewicz, Roland; Spatt, Josef; Moser, Hermann; Klein, Wolfhard; et al.
Abstract: Background and purpose: Successful long‐term treatment of spasticity in people with multiple sclerosis (pwMS) is challenging. We investigated the effects of multidisciplinary inpatient rehabilitation (MIR) and an individualized self‐training program delivered by an app on spasticity in pwMS. Methods: First, we assessed the efficacy of 4‐week MIR in ambulatory pwMS (Expanded Disability Status Scale < 7.0) with moderate to severe lower limb spasticity (defined by ≥4 points on the Numeric Rating Scale for spasticity [NRSs]) in a cohort of 115 pwMS at seven rehabilitation centers in Austria. In the case of a clinically relevant improvement in spasticity of ≥20% on the NRSs following MIR ( n = 94), pwMS were randomly allocated in a 1:1 ratio to either the newly designed MS‐Spasticity App or to a paper‐based self‐training program for 12 weeks. The primary outcome was change in NRSs (German Clinical Trials Registry DRKS00023960). Results: MIR led to a significant reduction of 2.0 points on the NRSs (95% confidence interval [CI] = 2.5–2.0, p < 0.000). MIR was further associated with a statistically significant improvement in spasticity on the Modified Ashworth Scale, strength, and all mobility outcomes. Following MIR, self‐training with the MS‐Spasticity App was associated with a sustained positive effect on the NRSs, whereas paper‐based self‐training led to a worsening in spasticity (median NRSs difference = 1.0, 95% CI = 1.7–0.3, p = 0.009). The MS‐Spasticity App was also associated with a significantly better adherence to self‐training (95% vs. 72% completion rate, p < 0.001). Conclusions: In pwMS, MIR is able to significantly improve lower limb spasticity, strength, and mobility. Following MIR, an individually tailored antispasticity program delivered by an app leads to sustained positive long‐term management. Abstract : In patients with multiple sclerosis, multidisciplinary inpatient rehabilitation (MIR) is able to significantly improve lower limb spasticity, strength, and mobility. Following MIR, an individually tailored antispasticity program delivered by an app leads to sustained positive long‐term management.